Influence of Job Burnout and Work Environment on Job Satisfaction and It’s Impact on Teachers Organizational Commitment - Rahmi Halimah; Yulihasri Yulihasri;; Harif Amali Rivai (Journal of Social Research, 2023)
Education is an important sector for improving human resources in a country. The teacher is one of the actors who has an important role in education. Teachers have a great responsibility to educate students in both knowledge and morals. Great responsibility makes teachers feel job burnout which will have an impact on job satisfaction and organizational commitment. In addition, the work environment also affects teacher job satisfaction and organizational commitment. In this study, a quantitative approach was used using Smart PLS to process data. Found in research this is job burnout, the work environment has a significant effect on organizational commitment. This study also found job satisfaction as a mediating variable of job burnout and work environment on organizational commitment. Based on the results and analysis of the research it was concluded that job burnout has a negative and significant effect on organizational commitment.